The effect of minocycline on novel object recognition memory and beta amyloid protein expression in alzheimer’s disease rat model - Poobalan, Kumararoobini (Universiti Sains Malaysia, 2016)
Alzheimer’s disease is a progressive neurodegenerative disorder which indicates gradual decline in cognitive impairment. It is the reason for mental and cognitive alteration such as low memory capacity, intellect and personality disorder and also behavioral changes in population older than the age of 65 (Saeed Sadigh-Eteghad, 2014) (Crew and Masliah 2010). This research study focuses mainly on the effect of minocycline on novel object recognition memory in Lipopolysaccharide (LPS) induced rats. Besides that, it is also to determine the effects of LPS administration on novel object recognition test and in Ap protein plaque deposition in rat brain. Administration of lipopolysaccharide (LPS) triggers neuroinflammation along with memory shortfall and leads to beta amyloid protein plaque deposition (Friihauf el al., 2015). Therefore, LPS- induced Sprague Dawley rat models were used as AD paradigm for this study in order to investigate the effect of minocycline on their memory impairment and beta amyloid protein plaque deposition. However the contribution of minocycline (microglial activation inhibitor) treatment in LPS- induced neuroinflammation AD model especially in in-vivo study is still unclear and need further investigation (Biscaro el al., 2012). The Novel Object Recognition (NOR) test is to evaluate the rat’s preference towards the novel object as to monitor its memory impairment of rats of various groups (Normal Saline, LPS, LPS with minocycline (50mg/kg), LPS with memantine (2mg/kg) treatment). 1st group consists of normal rats and the rest were injected with LPS. Then, the 3rd and 4th group were treated with minocycline and memantine respectively for 7 days consecutively. Based on histological finding, there were no beta amyloid deposition found in all of the rats. Hence, there is no data to analyze for investigating the significance. As the minocycline able to inhibit microglial activation which renders the further cognitive impairment while improving it, the LPS induced rats under minocycline treatment are anticipated to exhibit higher object recognition index than LPS induced rats. Besides that, LPS induced rats were assumed to show lower recognition index compared to normal rats to prove the memory impairment is due to LPS. The statistical analysis was done using One-Way Anova to analyze the recognition index produced by the four groups. According to the result, LPS induced rats under minocycline treatment shows the lowest value of recognition index among the other groups. In fact, none of the comparisons between groups were significant. However, LPS induced rats showed higher recognition index than normal rats as assumed. The minocycline treatment failed to produce the expected effect on NOR test. As the conclusion, the dose of minocycline was not optimum to recover the neuroinflammatory condition in rats. The dose optimization should have done to get the expected result. LPS successfully caused memory impairment even in the absence of beta amyloid protein. The drug, memantine treatment was successful in improving the rats’ memory.